2018
DOI: 10.1002/bsl.2370
|View full text |Cite
|
Sign up to set email alerts
|

The relations among animal abuse, psychological disorders, and crime: Implications for forensic assessment

Abstract: The confluence of developments in the assessment of animal abuse, the evolution of psychiatric nosology for the diagnosis of conduct disorder, legislative changes involving crimes against non-human animals, and the recent inclusion of crimes against animals in the FBI's National Incident-Based Reporting System, highlights the critical need for examining the forensic dimensions of animal abuse cases. We provide an overview of the research literature on these topics in the hope that forensic evaluators will have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…89,90 The Dark Triad significantly relates to psychopathy. The correlation of animal cruelty as well as the onset and probable influences to engage in animal cruelty can be understood by reviewing Ascione et al, 6 and Johnson. 7 Animal cruelty is a hallmark of psychopathy.…”
Section: The Dark Triadmentioning
confidence: 99%
“…89,90 The Dark Triad significantly relates to psychopathy. The correlation of animal cruelty as well as the onset and probable influences to engage in animal cruelty can be understood by reviewing Ascione et al, 6 and Johnson. 7 Animal cruelty is a hallmark of psychopathy.…”
Section: The Dark Triadmentioning
confidence: 99%
“…The definition of animal abuse (AA) that is now widely used in the academic literature to describe the symptom of conduct disorder (CD), that is analogous to the maltreatment of children, but perpetrated against animals, is "…non accidental, socially unacceptable behavior that causes pain, suffering or distress to and/or the death of an animal" (Ascione et al 2018;Ascione and Shapiro 2009). It is important to know about incidents of animal cruelty happening in our communities, not only because animal cruelty is a crime in all 50 states in the U.S. (Schaffner 2011), but also because, as noted above, there are many studies suggesting that those who engage in animal cruelty are also more likely to commit other crimes (Hoffer et al 2018;Ascione et al 2018;Johnson 2018). Previous work has shown that people who engage in animal cruelty have often been victims, themselves, of child abuse or have experienced other forms of family violence, such as witnessing another person committing an act of animal cruelty.…”
Section: Why Study Animal Cruelty?mentioning
confidence: 99%
“…Interest in the subject has grown in recent years, as more and more studies have revealed the links between those who engage in non-human animal (heretofore "animal") maltreatment and violence against people. By identifying crimes that co-occur with animal cruelty, it is thought that law enforcement officials could have another tool to try and prevent both animal cruelty and human violence (Hoffer et al 2018;Johnson 2018;Ascione et al 2018;Heide and Felthous 2018;Arkow and Lockwood 2016).…”
Section: Introductionmentioning
confidence: 99%
“…His research assessed the connection between animal cruelty to mental illness and, some researchers do similar research. Recently, animal cruelty became the current topic in DSM next edition, IV, IV-TR dan V, APA 1994, 2000(Ascione, McDonald, Tedeschi, & Williams, 2018.…”
Section: Animal Cruelty and Psychological Disorders Conduct Disorder (Cd)mentioning
confidence: 99%